Heterogeneous Effects of Tariff and Nontariff Policy Barriers in General Equilibrium - Peter Hannes Egger; Peter Egger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Most applied work in international economics treats trade policy (a) as a linear component of trade costs and (b) as an exogenous variable. This paper proposes a structural modelling approach that allows for the estimation of (possibly) non-parametric effects of trade policy using a propensity score method to account for the endogeneity bias of trade policy. The findings point to important nonlinear effects of tariff and nontariff policy. Specifically, they suggest that interdependencies between nontariff policy barriers and tariffs are an important determinant of the partial impact of a given policy change. Overall, trade policy changes seem to be effective only for low- and medium-tariff trade flows. In general equilibrium, loosening the linearity assumption translates to an increased heterogeneity of predicted trade effects with the mean and median effect being up to three times as large in a flexible, nonparametric specification.
Keywords: F14; F13; C14; 330